2008
DOI: 10.1016/j.cellsig.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

KIT associated intracellular tyrosines play an essential role in EpoR co-signaling

Abstract: KIT and erythropoietin receptor (EpoR) mediated co-signaling is essential for normal erythroid cell expansion, however the intracellular signals that contribute to cooperative signaling are poorly understood. Here, we examined the role of intracellular tyrosine residues in KIT and EpoR cooperation by co-expressing tyrosine (Y) to phenylalanine (F) and deletion mutants of KIT and EpoR in 32D cells. Of the four EpoR mutants examined, only EpoR-Y343 induced proliferation to near wildtype EpoR levels. A modest inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…In some cases, but not all, these types of heterotypic receptor interactions have been shown to correlate with cross-phosphorylation, e.g., SCF stimulation may promote tyrosine phosphorylation of the Epo or IL-7 receptor (123,300). In a study from Kapur's laboratory, it was demonstrated that mutation of seven tyrosine residues in the intracellular region of c-Kit abolished the ability of c-Kit to cooperate with Epo receptor, but interestingly adding back only the Src family kinase binding site in c-Kit restored cooperativity (111). Moreover, adding back the Src family binding site in combination with the PI3=-kinase binding site also allowed cooperatively between cKit and Epo receptor; however, this was inhibited by restoring both Src and PLC-␥ binding (111).…”
Section: F Interaction With Other Types Of Receptorsmentioning
confidence: 95%
See 1 more Smart Citation
“…In some cases, but not all, these types of heterotypic receptor interactions have been shown to correlate with cross-phosphorylation, e.g., SCF stimulation may promote tyrosine phosphorylation of the Epo or IL-7 receptor (123,300). In a study from Kapur's laboratory, it was demonstrated that mutation of seven tyrosine residues in the intracellular region of c-Kit abolished the ability of c-Kit to cooperate with Epo receptor, but interestingly adding back only the Src family kinase binding site in c-Kit restored cooperativity (111). Moreover, adding back the Src family binding site in combination with the PI3=-kinase binding site also allowed cooperatively between cKit and Epo receptor; however, this was inhibited by restoring both Src and PLC-␥ binding (111).…”
Section: F Interaction With Other Types Of Receptorsmentioning
confidence: 95%
“…In a study from Kapur's laboratory, it was demonstrated that mutation of seven tyrosine residues in the intracellular region of c-Kit abolished the ability of c-Kit to cooperate with Epo receptor, but interestingly adding back only the Src family kinase binding site in c-Kit restored cooperativity (111). Moreover, adding back the Src family binding site in combination with the PI3=-kinase binding site also allowed cooperatively between cKit and Epo receptor; however, this was inhibited by restoring both Src and PLC-␥ binding (111). Also, the synergistic interaction between c-Kit and GM-CSF receptor may involve transphosphorylation; GM-CSF by itself did not promote c-Kit phosphorylation, but concurrent treatment with both SCF and GM-CSF did result in a stronger c-Kit phosphorylation compared with SCF by itself (127), although other studies have failed to demonstrate this (162).…”
Section: F Interaction With Other Types Of Receptorsmentioning
confidence: 98%
“…55 However, studies using EpoR tyrosine-mutants demonstrated that PI3K/Akt activation is also indirectly mediated via Y343, involving the adaptor Gab2. 37,55,56 Stat5 and Akt pathways are thus coupled in EpoR signaling and might cooperate in target gene activation. Interestingly, we could show that KIT murine embryonic stem cells as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kit and Epo-R cross-receptor activation is reported to be necessary for normal erythroid cell expansion. [22][23][24][25][26] Previous in vivo analyses using Kit and c C mutant mice revealed synergistic effects of Kit and c C signaling in thymopoiesis. 27,28 In natural killer cells, activation of Kit and IL-2/15 signaling causes synergy in proliferation through enhanced mitogen-activated protein kinase activity.…”
Section: Discussionmentioning
confidence: 99%